Spontaneous remission of retinal capillary macroaneurysm: case report - Lu, Shui; Meng, Xiaomei; Chen, Tiantian; Zhang, Zhengwei (Frontiers in Medicine, 2025)
BackgroundRetinal capillary macroaneurysms (RCM), a rare macular vascular disease, was reported here for the first time in a Chinese patient.Case presentationA 68-year-old female patient presented with a complaint of blurred vision in her right eye for over a month. Upon specialized examination, her best-corrected visual acuity (BCVA) was 20/50 in the right eye. Fundus examination revealed yellow-white, hard exudates in the nasal and temporal sides of the fovea and a suspected hemorrhagic lesion was observed external to the inferior vascular arcade. Optical coherence tomography (OCT) scanning through the foveal center revealed a serous neurosensory detachment with intraretinal hard exudates. A preliminary diagnosis of chronic branch retinal vein occlusion (BRVO) in the right eye was made. To alleviate the macular serous detachment, the treatment plan was intravitreal injection of conbercept once a month. One month after the first injection, the patient reported worsening symptoms. BCVA in the right eye decreased to 20/100, and fundus examination revealed a ring-shaped yellow-white, fine, hard exudates surrounding the initial lesion. Two more intravitreal injections were given one month apart. Subsequently, intravitreal injections were discontinued due to inadequate therapeutic efficacy and considerations regarding treatment costs. Approximately 10 months after the last intravitreal injection, the patient reported improved vision. Optical coherence tomography angiography (OCTA) revealed a vertical oval tubular structure with a hyperreflective wall external to the inferior vascular arcade, with blood flow signals at the top of the lumen. Six more months later, the patient reported stable vision. OCTA still showed a vertical oval tubular structure, and the lumen diameter had increased. One more year later, the patient had a follow-up and the BCVA was 20/20 in both eyes. OCTA showed complete closure of the aneurysm without any abnormal blood flow. The right eye was conclusively diagnosed with RCM.ConclusionThis report presented the first documented Chinese case of isolated RCM. Although the lesion initially enlarged after three intravitreal injections of conbercept, it eventually resolved spontaneously. This outcome suggested that close observation may be appropriate for RCM patients with stable, good vision if such patients are unwilling or afraid to receive laser treatment.